1991
DOI: 10.1007/bf00231466
|View full text |Cite
|
Sign up to set email alerts
|

Misdirections in slow goal-directed arm movements and pointer-setting tasks

Abstract: Information about the direction of the virtual line between two positions in space (directional information) is used in many decision-making and motor tasks. We investigated how accurately directional information is processed by the brain. Subjects performed two types of task. In both tasks they sat at a table. In the first task they had to move their hand slowly and accurately from an initial position 40 cm in from of them to visually presented targets at a distance of 30 cm from the initial position (movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(27 citation statements)
references
References 8 publications
5
22
0
Order By: Relevance
“…In a series of studies of spatial working memory where subjects had to memorize the location of a dot within a circle and then use a pen to draw the dot in an empty circle, Huttenlocher et al (1991) observed a systematic directional error toward the oblique directions and away from the cardinal directions in a reference frame originating at the center of the circle. We observed a similar systematic directional error for movement end points when subjects made fast movements to the location of previously seen targets located in the periphery of an imaginary circle in a center out task (Smyrnis et al 2000;Gourtzelidis et al 2001), and de Graaf et al (1991, 1994 observed a comparable error in the initial heading direction when moving slowly or pointing toward a visual target in a similar center out task. Krukowski and Stone (2005) observed the systematic directional error in the heading of smooth eye pursuit, and Koehn et al (2008) observed the corresponding error pattern for antisaccade end points using the same reference frame.…”
Section: Introductionsupporting
confidence: 61%
“…In a series of studies of spatial working memory where subjects had to memorize the location of a dot within a circle and then use a pen to draw the dot in an empty circle, Huttenlocher et al (1991) observed a systematic directional error toward the oblique directions and away from the cardinal directions in a reference frame originating at the center of the circle. We observed a similar systematic directional error for movement end points when subjects made fast movements to the location of previously seen targets located in the periphery of an imaginary circle in a center out task (Smyrnis et al 2000;Gourtzelidis et al 2001), and de Graaf et al (1991, 1994 observed a comparable error in the initial heading direction when moving slowly or pointing toward a visual target in a similar center out task. Krukowski and Stone (2005) observed the systematic directional error in the heading of smooth eye pursuit, and Koehn et al (2008) observed the corresponding error pattern for antisaccade end points using the same reference frame.…”
Section: Introductionsupporting
confidence: 61%
“…Similarly, related errors have also been observed for hand pointing to visually acquired azimuth target [14], [16], [23]. A model-based interpretation of the direction misjudgments in this and the prior studies in [20] and [21] will be reported elsewhere.…”
Section: B Directional Componentssupporting
confidence: 71%
“…Open-loop response errors, such as those reported here, however, can be diminished by improving visual or kinesthetic feedback from the virtual or remote environment pointing task (e.g., [23]). This feedback may aid in correcting rotational misjudgments induced by inaccurate tracking and rendering of the operator's head roll angle.…”
Section: Implications For Ve and Telepresence Systemsmentioning
confidence: 66%
“…The origin of such curvature has been explained in many ways, for example by the biomechanics of the arm [1], a perceptual distortion of space [2,3,4], or a misjudgment in direction [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by de Graaf et al [5] participants made movements in a horizontal plane from a start position towards visually presented targets, and set the orientation of a pointer at the same start position to point towards the targets. These authors found that the initial direction of the movement deviated systematically from a straight line, and that a similar pattern of errors was made in setting the pointer.…”
Section: Introductionmentioning
confidence: 99%